PENYELESAIAN SENGKETA ATAS KEPEMILIKAN TANAH ADAT BERDASARKAN HUKUM ADAT (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2023)
Abstract The history of land law in Indonesia prior to the enactment of the UUPA apart from western agrarian law, namely customary law. It includes customary rights, property rights and usufructuary rights. As one of the essential elements forming the State, land plays a vital role in the life and livelihood of the nation supporting the State concerned, especially those whose agrarian style is dominant. Customary land law itself is different in each region because each region has different customary sources. Customary land law is the law that regulates land rights that apply in each region. The existence of customary courts in resolving land disputes in positive law has been revoked, because according to the Law on Judicial Power (UUKK) it is no longer recognized that courts are conducted by non-state judicial bodies, meaning that all courts throughout the territory of the Republic of Indonesia are state courts stipulated by law. Law, although in practice in the field it is found customary courts of a local nature. The policy of unification of the judiciary is one of the reasons why customary justice is slowly being abandoned. The Law on Judicial Power (UUKK) opens the possibility of peaceful settlement of civil cases as a spirit that is manifested in the civil justice system. This research was conducted with the aim of knowing the position and existence of customary courts in the context of resolving land disputes and resolving land disputes in indigenous peoples. Keywords: Customary Courts; Customary Land; Dispute